Interictal Slow and High-Frequency Oscillations: Is it an Epileptic Slow or Red Slow?. Issue 2 (March 2019) - Inoue, Takeshi; Inouchi, Morito; Matsuhashi, Masao; Matsumoto, Riki; Hitomi, Takefumi; Daifu-Kobayashi, Masako; Kobayashi, Katsuya; Nakatani, Mitsuyoshi; Kanazawa, Kyoko; Shimotake, Akihiro; Kikuchi, Takayuki; Yoshida, Kazumichi; et al.
Abstract : Purpose: We reported the presence of interictal slow and high-frequency oscillations (HFOs) (IIS + HFO) and its temporal change so as to elucidate its clinical usefulness as a surrogate marker of epileptogenic zone in a patient with intractable focal epilepsy. Methods: We focused on one of the core electrodes of epileptogenicity, and investigated IIS + HFO in the pre- and post-segment of 30 minutes to all the 6 seizures. We adopted interictal slow in duration of 0.33 to 10 seconds, amplitude ≥50 μV and co-occurring with HFOs, and then divided into 5 groups depending on the amplitude of slow wave. Results: Before and after all the 6 seizures, the number of IIS + HFO was 2, 890 at one electrode in the core epileptogenic zone. The number of IIS + HFO significantly decreased for 30 minutes after seizures. Furthermore, the number of IIS + HFO with the amplitude of 200 to 399 μV significantly decreased after seizures. Conclusions: IIS + HFO with the amplitude of 200 to 399 μV was influenced by and decreased after seizures. It may reflect the core part of epileptogenic area as similarly as ictal direct current shifts and ictal HFOs do. IIS + HFO could be called as the term "red slow, " which may be useful to delineate at least a part of the epileptogenic zone. Abstract : Supplemental Digital Content is Available in the Text.